Health Consequences of Service During the Persian Gulf War: Initial Findings and Recommendations for Immediate Action - Institute of Medicine (The National Academies Press, 1995)
This initial volume in an ongoing study of the potential health consequences of service during the Persian Gulf War responds to a request from Congress to determine whether actions taken to evaluate health effects have been appropriate. It reflects the committee's examination of health outcomes and related research efforts, women's health and reproductive health issues, infrastructure and procedures for data collection, health services influences, the role of psychiatric diagnosis, and a review of the activities of boards and coordinating groups, as well as how issues stemming from involvement in the Persian Gulf might be relevant for possible future conflicts. While the committee continues its full-length study of the problem, the recommendations in this volume are for actions it feels should be taken immediately.
Keywords: Health and Medicine

Guidelines for Chemical Warfare Agents in Military Field Drinking Water (The National Academies Press, 1995)
Keywords: Environment and Environmental Studies

Adverse Reproductive Outcomes in Families of Atomic Veterans: The Feasibility of Epidemiologic Studies - Institute of Medicine (The National Academies Press, 1995)
Over the past several decades, public concern over exposure to ionizing radiation has increased. This concern has manifested itself in different ways depending on the perception of risk to different individuals and different groups and the circumstances of their exposure. One such group are those U.S. servicemen (the "Atomic Veterans" who participated in the atmospheric testing of nuclear weapons at the Nevada Test Site or in the Pacific Proving Grounds, who served with occupation forces in or near Hiroshima and Nagasaki, or who were prisoners of war in or near those cities at the time of, or shortly after, the atomic bombings. This book addresses the feasibility of conducting an epidemiologic study to determine if there is an increased risk of adverse reproductive outcomes in the spouses, children, and grandchildren of the Atomic Veterans.
Keywords: Health and Medicine; Environment and Environmental Studies

Recommendations for Research on the Health of Military Women: Bibliographies - Institute of Medicine (The National Academies Press, 1995)
Keywords: Health and Medicine

HIV and the Blood Supply: An Analysis of Crisis Decisionmaking - Institute of Medicine (The National Academies Press, 1995)
During the early years of the AIDS epidemic, thousands of Americans became infected with HIV through the nation's blood supply. Because little reliable information existed at the time AIDS first began showing up in hemophiliacs and in others who had received transfusions, experts disagreed about whether blood and blood products could transmit the disease. During this period of great uncertainty, decision-making regarding the blood supply became increasingly difficult and fraught with risk. This volume provides a balanced inquiry into the blood safety controversy, which involves private sexual practices, personal tragedy for the victims of HIV/AIDS, and public confidence in America's blood services system. The book focuses on critical decisions as information about the danger to the blood supply emerged. The committee draws conclusions about what was done—and recommends what should be done to produce better outcomes in the face of future threats to blood safety. The committee frames its analysis around four critical area:
Keywords: Health and Medicine

Evaluation of the Army's Draft Assessment Criteria to Aid in the Selection of Alternative Technologies for Chemical Demilitarization (The National Academies Press, 1995)
Keywords: Environment and Environmental Studies

The Development of Medications for the Treatment of Opiate and Cocaine Addictions: Issues for the Government and Private Sector - Institute of Medicine (The National Academies Press, 1995)
Pharmacotherapy, as a means of treating drug addiction in combination with other treatment modalities, has received too little attention from the research community, the pharmaceutical industry, public health officials, and the federal government. Medications to combat drug addiction could have an enormous impact on the medical consequences and socioeconomic problems associated with drug abuse, both for drug-dependent individuals and for American society as a whole. This book examines the current environment for and obstacles to the development of anti-addiction medications, specifically those for treating opiate and cocaine addictions, and proposes incentives for the pharmaceutical industry that would help overcome those obstacles and accelerate the development of anti-addiction medications.
Keywords: Health and Medicine

Health Services Research: Work Force and Educational Issues - Institute of Medicine (The National Academies Press, 1995)
In a health care environment undergoing major restructuring, health services researchers have an important contribution to make in evaluating the impact of change and in guiding policymakers, clinicians, corporate purchasers, and patients. This book examines the health services research work force and its education. Conclusions focus on the quantity and quality of the work force, prospects for the future, and directions for government policy.
Keywords: Health and Medicine

Review of the Fialuridine (FIAU) Clinical Trials - Institute of Medicine (The National Academies Press, 1995)
In June 1993 a clinical trial of fialuridine (FIAU), a promising new medication for hepatitis B, was abruptly terminated when one of the 15 out-patients participating in the National Institutes of Health (NIH) study was suddenly hospitalized with liver failure. Although all the remaining patients were contacted and told to stop taking their medication, six more subsequently developed severe toxicity. Five patients died, and two others were probably saved from death only by having liver transplants. In response to a request from the Secretary of the Department of Health and Human Services, the IOM committee has analyzed the FIAU clinical trials, making recommendations for additional safeguards for the conduct of future clinical trials. This evaluation included the review of documents pertaining to investigational new drug submissions, protocols and consent forms from other clinical trials, as well as information available from other clinical and preclinical experience with compounds related to FIAU and its parent drug, fiacitibine (FIAC), which is metabolized to FIAU. The committee does not seek to affix responsibility for the adverse outcome of this NIH trial, but instead focuses on whether any rules or procedures governing the clinical trials process itself need to be changed, and if so, what burdens or costs such changes might place on future clinical trials.
Keywords: Health and Medicine

Allocating Federal Funds for Science and Technology - Institute of Medicine; National Academy of Sciences; National Academy of Engineering; National Research Council (The National Academies Press, 1995)
The United States faces a new challenge—maintaining the vitality of its system for supporting science and technology despite fiscal stringency during the next several years. To address this change, the Senate Appropriations Committee requested a report from the National Academies of Sciences and Engineering and the Institute of Medicine to address "the criteria that should be used in judging the appropriate allocation of funds to research and development activities; to examine the appropriate balance among different types of institutions that conduct such research; and to look at the means of assuring continued objectivity in the allocation process." In this eagerly-awaited book, a committee of experts selected by the National Academies and the Institute responds with 13 recommendations that propose a new budgeting process and formulates a series of questions to address during that process. The committee also makes corollary recommendations about merit review, government oversight, linking research and development to government missions, the synergy between research and education, and other topics. The recommendations are aimed at rooting out obsolete and inadequate activities to free resources from good programs for even better ones, in the belief that "science and technology will be at least as important in the future as they have been in the past in dealing with problems that confront the nation." The authoring committee of this book was chaired by Frank Press, former President of the National Academy of Sciences (1981-1993) and Presidential Science and Technology Advisor (1977-1981).
Keywords: Policy for Science and Technology; Industry and Labor

Dental Education at the Crossroads: Challenges and Change - Institute of Medicine (The National Academies Press, 1995)
Six dental schools have closed in the last decade and others are in jeopardy. Facing this uncertainty about the status of dental education and the continued tension between educators and practitioners, leaders in the profession have recognized the need for purpose and direction. This comprehensive volume—the first to cover the education, research, and patient care missions of dental schools—offers specific recommendations on oral health assessment, access to dental care, dental school curricula, financing for education, research priorities, examinations and licensing, workforce planning, and other key areas. Well organized and accessible, the book:
Keywords: Education; Health and Medicine

Federal Regulation of Methadone Treatment - Institute of Medicine (The National Academies Press, 1995)
For nearly three decades, methadone hydrochloride has been the primary means of treating opiate addiction. Today, about 115,000 people receive such treatment, and thousands more have benefited from it in the past. Even though methadone's effectiveness has been well established, its use remains controversial, a fact reflected by the extensive regulation of its manufacturing, labeling, distribution, and use. The Food and Drug Administration regulates the safety and effectiveness of methadone, as it does for all drugs, and the Drug Enforcement Administration regulates it as a controlled substance. However, methadone is also subjected to a unique additional tier of regulation that prescribes how and under what circumstances it may be used to treat opiate addiction. Federal Regulation of Methadone Treatment examines current Department of Health and Human Services standards for narcotic addiction treatment and the regulation of methadone treatment programs pursuant to those standards. The book includes an evaluation of the effect of federal regulations on the provision of methadone treatment services and an exploration of options for modifying the regulations to allow optimal clinical practice. The volume also includes an assessment of alternatives to the existing regulations.
Keywords: Health and Medicine

Measuring Poverty: A New Approach - National Research Council (The National Academies Press, 1995)
Each year's poverty figures are anxiously awaited by policymakers, analysts, and the media. Yet questions are increasing about the 30-year-old measure as social and economic conditions change. In Measuring Poverty a distinguished panel provides policymakers with an up-to-date evaluation of:
Keywords: Industry and Labor; Health and Medicine; Behavioral and Social Sciences

Environmental Medicine: Integrating a Missing Element into Medical Education - Institute of Medicine (The National Academies Press, 1995)
People are increasingly concerned about potential environmental health hazards and often ask their physicians questions such as: "Is the tap water safe to drink?" "Is it safe to live near power lines?" Unfortunately, physicians often lack the information and training related to environmental health risks needed to answer such questions. This book discusses six competency based learning objectives for all medical school students, discusses the relevance of environmental health to specific courses and clerkships, and demonstrates how to integrate environmental health into the curriculum through published case studies, some of which are included in one of the book's three appendices. Also included is a guide on where to obtain additional information for treatment, referral, and follow-up for diseases with possible environmental and/or occupational origins.
Keywords: Health and Medicine

Sources of Medical Technology: Universities and Industry - Institute of Medicine (The National Academies Press, 1995)
Evidence suggests that medical innovation is becoming increasingly dependent on interdisciplinary research and on the crossing of institutional boundaries. This volume focuses on the conditions governing the supply of new medical technologies and suggest that the boundaries between disciplines, institutions, and the private and public sectors have been redrawn and reshaped. Individual essays explore the nature, organization, and management of interdisciplinary R&D in medicine; the introduction into clinical practice of the laser, endoscopic innovations, cochlear implantation, cardiovascular imaging technologies, and synthetic insulin; the division of innovating labor in biotechnology; the government- industry-university interface; perspectives on industrial R&D management; and the growing intertwining of the public and proprietary in medical technology.
Keywords: Health and Medicine; Industry and Labor

Real People Real Problems: An Evaluation of the Long-Term Care Ombudsman Programs of the Older Americans Act - Institute of Medicine (The National Academies Press, 1995)
Keywords: Behavioral and Social Sciences

Information Technology for Manufacturing: A Research Agenda - National Research Council (The National Academies Press, 1995)
This book describes a vision of manufacturing in the twenty-first century that maximizes efficiencies and improvements by exploiting the full power of information and provides a research agenda for information technology and manufacturing that is necessary for success in achieving such a vision. Research on information technology to support product and process design, shop-floor operations, and flexible manufacturing is described. Roles for virtual manufacturing and the information infrastructure are also addressed. A final chapter is devoted to nontechnical research issues.
Keywords: Industry and Labor; Computers and Information Technology

Not Eating Enough: Overcoming Underconsumption of Military Operational Rations - Institute of Medicine (The National Academies Press, 1995)
Eating enough food to meet nutritional needs and maintain good health and good performance in all aspects of life—both at home and on the job—is important for all of us throughout our lives. For military personnel, however, this presents a special challenge. Although soldiers typically have a number of options for eating when stationed on a base, in the field during missions their meals come in the form of operational rations. Unfortunately, military personnel in training and field operations often do not eat their rations in the amounts needed to ensure that they meet their energy and nutrient requirements and consequently lose weight and potentially risk loss of effectiveness both in physical and cognitive performance. This book contains 20 chapters by military and nonmilitary scientists from such fields as food science, food marketing and engineering, nutrition, physiology, psychology, and various medical specialties. Although described within a context of military tasks, the committee's conclusions and recommendations have wide-reaching implications for people who find that job-related stress changes their eating habits.
Keywords: Health and Medicine; Food and Nutrition

Nursing, Health, and the Environment - Institute of Medicine (The National Academies Press, 1995)
America's nurses, an estimated 2 million strong, are often at the frontlines in confronting environmental health hazards. Yet most nurses have not received adequate training to manage these hazards. Nursing, Health, and the Environment explores the effects that environmental hazards (including those in the workplace) have on the health of patients and communities and proposes specific strategies for preparing nurses to address them. The committee documents the magnitude of environmental hazards and discusses the importance of the relationship between nursing, health, and the environment from three broad perspectives:
Keywords: Health and Medicine

Infectious Diseases in an Age of Change: The Impact of Human Ecology and Behavior on Disease Transmission - Roizman, Bernard (The National Academies Press, 1995)
Twenty-first century progress against infectious diseases is threatened by urbanization, population growth, war refugees, changing sexual standards, and a host of other factors that open doors to the transmission of deadly pathogens. Infectious Diseases in an Age of Change reports on major infectious diseases that are on the rise today because of changing conditions and identifies urgently needed public health measures. This volume looks at the range of factors that shape the epidemiology of infectious diseases—from government policies to economic trends to family practices. Describing clinical characteristics, transmission, and other aspects, the book addresses major infectious threats—sexually transmitted diseases, Lyme disease, human cytomegalovirus, diarrheal diseases, dengue fever, hepatitis viruses, HIV, and malaria. The authors also look at the rising threat of drug-resistant strains of tuberculosis, rapid exhaustion of the weapons to fight bacterial infections, and prospects for vaccinations and eradication of pathogens. Infectious Diseases in an Age of Change will be important to public health policymakers, administrators, and providers as well as epidemiologists and researchers.
Keywords: Health and Medicine